POLA PERSEBARAN PEMANFAATAN KAWASAN HUTAN OLEH MASYARAKAT LOKAL DI NAGARI AIA LUO KECAMATAN PAYUNG SEKAKI KABUPATEN SOLOK - Rifki Anugrah Ramadhan; Endah Purwaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine: 1) The distribution pattern of forest area utilization by local residents. 2) Forest area utilization through land suitability evaluation. This study used a survey method with a quantitative approach in Nagari Aia Luo, Payung Sekaki District, Solok Regency. Data collection was conducted directly in the field to determine the coordinates of forest utilization areas by local residents and to determine how the areas are utilized. This study yielded the following findings: 1) The distribution pattern of forest utilization areas by local residents is clustered with an NNR value of 0.544470, and no utilization areas were found in protected forest areas. 2) Based on the map processed using the fuzzy method, the Aia Luo region is dominated by areas classified as less suitable for the commodities currently planted. Based on the land suitability assessment conducted in the area, the community can choose an alternative commodity, white soybeans, with the suitable classification dominating most of the area.